(untitled) (Konturen, 2019)
The following reflections contribute to an exploration of the “peacetime crimes” in Ingeborg Bachmann’s work by offering an analysis of an episode in her novel Malina. Tracing a hitherto unnoticed allusion to a poem by Ungaretti, the analysis also contributes to a discussion of Bachmann’s poetics of citation. The subtle web of intertextual play and citation that pervades the whole novel de-emphasizes the role of the author in literary history and opens instead a reading space where literature as textual memory, again and again, comes to be actualized.